Rapid Intravenous Rehydration in the Treatment of Acute Infantile Diarrhoea with Severe Dehydration - Sunoto, Sunoto (Indonesian Pediatric Society, 1990)
During a 6-month-period from July to December 1989, 21 patients below 2 years of age hospitalized at the Department of Child Health, Medical School, University of Indonesia Jakarta, with acute diarrhoea and severe dehydration had been studied. The mean age was 9.21 months with the mean body weight of 6.732 grams. No accompanying diseases nor complications were found in these patients. The patients were treated with rapid i.v. rehydration using RL solution 70 mL/kg/3 hours, followed by ORS and continued by feeding. After a 3- hour-period the average body weight increased by 6.71%, fourteen patients had been rehydrated whereas the rest were still in mild dehydration which could be rehydrated by ORS. Clinical and laboratory examinations revealed improvement of the condition in all o patients. No complications nor death occur in this study. Compared to the earlier method by Sutedjo et al. (1960) and the recommendation of the First National Seminar on Rehydration in 1974, i.e. 30 mL/kg/hr in the first hour and 10 mL/kg/hr in the next 7 hours, this method is better, simpler, easier, shorter, practical and thus lessened the cost of hospitalization, i.e. US 22.17 per patient with an average of hospital stay of 2.76 days only.